The long term effects of legalizing divorce on children - Libertad González; Tarja K. Viitanen (Institute for the Study of Labor (IZA), 2008)
We estimate the effect of divorce legalization on the long-term well-being of children. Our identification strategy relies on exploiting the different timing of divorce legalization across European countries. Using European Community Household Panel data, we compare the adult outcomes of cohorts who were raised in an environment where divorce was banned with cohorts raised after divorce was legalized in the same country. We also have control countries where all cohorts were exposed (or not exposed) to divorce as children, thus leading to a difference-in-differences approach. We find that women who grew up under legal divorce have lower earnings and income as well as worse health as adults compared with women who grew up under illegal divorce. These effects are not found for men. We find no effects of divorce legalization on children's family formation or dissolution patterns.
Keywords: J12; 330; Divorce; legislation; intergenerational effects; child outcomes; Scheidung; Eherecht; Kinder; Generationenbeziehungen; Lebensqualität; Geschlecht; EU-Staaten